Endoscopic malleus button hole myringoplasty - Prinja, Sumit; Singh, Gurbax; Davessar, Jai Lal; Parmar, Suchina; Singh, Ramandeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Myringoplasty or type-1 tympanoplasty is surgical procedure that is used for repair of the tympanic membrane. The result outcome of myringoplasty depends on several variables such as method of tympanoplasty taken whether endoscopic and microscopic, of size of perforation, bony overhang, eustachian tube function, state of the middle ear mucosa, degree of pneumatization of mastoid and technique of graft placement. Methods: Our study was conducted at G.G.S. Medical College, Faridkot from January 2017 to April 2018. Patients were taken for endoscopic tympanoplasty and graft was placed with buttonhole technique. Results were compared in form of preoperative audiometry and post-operative audiometry done after 3 months. Results: In our study patients done with endoscopic tympanoplasty with buttonhole technique graft placement showed postoperative audiometry with decreased air bone gap till 10 db in maximum number of patients and 97% patents with graft uptake. Conclusions: The use of endoscopes has brought a new perspective to ear surgery. The use of endoscopes along with different technique as mentioned of placing graft to prevent all the complications.